Implementation of solar PV system unified ZSI-based dynamic voltage restorer with U-SOGI control scheme for power quality improvement. (2nd July 2020) - Jayakumar, T.; Alexander Stonier, Albert
Abstract : The main challenge in today's power system is to supply continuous, reliable power and satisfy the high demand. The incorporation of renewable energy sources into the utility grid system can be accomplished. However, the renewable sources are intermittent in nature and the loads work dynamically and cause imbalances to the system voltage within an immediate time. Intermittent renewable sources affect the voltage of the power grid system. Photovoltaic (PV) power generation with Z-source inverter (ZSI)-based dynamic voltage restorer (DVR) is used to avoid that. For step-up low DC voltage to required AC voltage for the compensation of the voltage disturbance, ZSI with the energy storage impedance network is used. DC-DC converters connect the PV cell and the battery storage to the impedance source network. This article also incorporates an upgraded second-order generalized integrator (U-SOGI) control system for the generation of reference voltage signals. The U-SOGI control reference voltage generation approach greatly improves system performance and decreases the harmonic voltage. The voltage-related problems in the system connected to the utility grid are mitigated with DVR. In different load and source conditions, the PV generation with DVR performance is verified by the digital simulation and experimental prototype.